High-fat diet-induced intestinal dysbiosis is associated with the exacerbation of Sjogren’s syndrome - Zhang, Minjie; Liang, Yichen; Liu, Yanbo; Li, Yixuan; Shen, Long; Shi, Guixiu (Frontiers in Microbiology, 2022)
Environmental factors are believed to influence the evolution of primary Sjögren’s syndrome (pSS). The aims of this study were to investigate the association of pSS with high fat diet (HFD) and to relate HFD induced gut dysbiosis to pSS exacerbation. Male Wild Type (WT) and IL-14α transgenic mice (IL-14α TG) mice were fed a standard diet (SD) and HFD for 11 months. We found the increase of autoantibody level, more severe dry eye, and dry mouth symptom, earlier presence of systemic features in the IL-14α TG mice treated HFD. This data suggests that HFD can promote the process of pSS in the IL-14α TG mice. In addition, HFD lead to a decrease in the richness and diversity of gut microbiota of IL-14α TG mice treated HFD. The abundance of Deferribacterota was significantly enriched in the IL-14α TG mice treated HFD compared with other groups. Through Mental test between gut microbiota and clinical parameters, we found that HFD induced the dysbiosis gut microbiota were associated with pSS clinical parameters. In conclusion, HFD results in the aggravation of pSS progression, likely due to the increase of potentially pathogenic microorganisms.